Formation of Students' Religious Character Through Habituation of Religious Activities - M. Mahbubi; Holifatul hasanah (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to analyze the formation of religious character of students at SMP Bhakti Pertiwi through the habituation method, by instilling religious values in everyday life. The approach used is qualitative with a case study method, where data is collected through observation and interviews. The results of the study indicate that the religious character of students is formed through various religious activities, such as learning the Qur'an, praying in congregation, tausiah, sunnah prayers, istighosah, and monthly motivational Quranic gathering activities. The factors that influence the formation of religious character include the family environment, school environment, social environment, and the influence of social media. Character formation through the habituation method also has a positive impact on students, so that they are able to internalize religious values, both in the school environment and outside of school.